Moringa oleifera Leaf Meal: A Sustainable Approach for Poultry Production: A Review - , Manju Lata; , B.C. Mondal (Archives of Current Research International, 2024)
Poultry production is among the fastest ways to address the shortage of animal protein supply and intake in many nations. With the prohibition of antibiotics as growth promoters in the poultry industry due to rising bacterial resistance and growing public concern over health and food safety, the sector has been prompted to seek safe alternatives. This shift has led to a focus on finding natural antibiotic substitutes and optimizing feed management to enhance chicken health and growth. Consequently, phytogenics have emerged as promising natural alternatives to antibiotics in the poultry sector. Moringa oleifera has attracted significant research interest recently as a natural supplement with numerous health advantages for poultry. Known for its antimicrobial, antioxidant, anti-inflammatory, and cholesterol-lowering properties, Moringa also aids in activating digestive enzymes in the stomach due to its wealth of bioactive compounds. This review emphasizes the potential impact of Moringa oleifera as a natural feed additive on growth performance, nutrient digestibility, blood biochemical profile, antioxidant effects, immune response, and egg production in poultry.